THE CHEMICAL COMPOSITION AND VARIOUS SAMPLES PREPARATION METHODS FOR In Vitro GAS TEST OF TWO TROPICAL FEEDS - Daryatmo, J.; Kustantinah, K.; Orskov, E.R. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
A 3x2 factorial experimental design was conducted to evaluate the chemical composition ofSesbania grandiflora (SG) and Manihot esculenta Crantz (MEC) leaves and to measure the effects ofpreparation and drying methods on the in vitro gas production in the presence and absence of PEG. Thecollected samples were divided into three groups: One group was fresh samples (F). The second groupwas oven-dried at 55°C for 48h (OD) and the last group was freeze-dried at –40°C for 72h (FD). Resultsshowed that the mean value of gas production from fresh SG and MEC samples were not significantlyhigher (P<0.05) than from FD and OD samples. In SG and MEC, the mean value of gas production ofFD was not significant compared to OD samples (P>0.05). Gas production from samples added withPEG were higher (P<0.05) than without PEG. In conclusion, the preparation and drying methods of feedsamples could affect the volume of gas production. The addition of PEG in SG and MEC resulted inhigher gas production volumes.